Automated Flow Injection Chromatography for the Rapid Assay of Parabens in Hygiene Wipes. (23rd March 2016) - Kondylis, Panagiotis; Barbatsi, Margarita; Economou, Anastasios
ABSTRACT: A fully automated flow injection chromatography (FIC) instrument and method are reported for the determination of methylparaben and propylparaben. The system consisted of a computer-controlled MilliGAT precision pump, a six–way injection valve, a peristaltic pump, a monolithic column, and an ultraviolet absorbance detector. The mobile phase composition, flow rate, and sample volume were optimized. The method was fully validated; the calibration plots were linear from 1.0 × 10 −6 to 5.0 × 10 −5 mol L −1 for both parabens. The limits of detection were 1.0 × 10 −7 mol L −1 for methylparaben and 3.0 × 10 −7 mol L −1 for propylparaben. The recoveries for both parabens were 97% and the interlaboratory reproducibility was 2.4% for methylpareben and 4.1% for propylparaben at 1.0 × 10 −5 mol L −1 . The method was employed for the determination of methylparaben and propylparaben in hygiene wipes.